1980
DOI: 10.1038/bjc.1980.5
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole: evidence for activity on human haemopoietic progenitor cells

Abstract: Summary.-Levamisole, which has immunostimulant activity, is now being used to treat some forms of cancer. We report that the drug enhances granulocyte colony formation. The mechanism of action appears to be partly through modulation of molecules on cell membranes. The molecular content of colony-stimulating activity (CSA) released into leucocyte-conditioned medium by cells of leukaemic and some preleukaemic patients can be quantitatively altered by levamisole, both in vitro and in vivo, but the CSA produced is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Evidence is available that LMS may favor marrow restoration after chemotherapy [10]. Also, enhanced granulopoietic colony formation was observed when LMS was cocultured with human bone marrow stem cells in leukocyte-conditioned medium through promoting the release of colony-stimulating activity [11]. Previously, we reported the short-term effectiveness of CSA&LMS regimen in a small group of patients with refractory or relapsed SAA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is available that LMS may favor marrow restoration after chemotherapy [10]. Also, enhanced granulopoietic colony formation was observed when LMS was cocultured with human bone marrow stem cells in leukocyte-conditioned medium through promoting the release of colony-stimulating activity [11]. Previously, we reported the short-term effectiveness of CSA&LMS regimen in a small group of patients with refractory or relapsed SAA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Early evidence showed that LMS favored marrow restoration [17] and enhanced the numbers of granulocyte colony units [18]. More importantly, up to 91.5% of moderate AA responded to a novel immunosuppressive strategy of CsA alternately combined with LMS (CsA + LMS regimen) in our pilot study [19].…”
Section: Introductionmentioning
confidence: 82%
“…Levamisole (LMS), originally designed for anthelminthic applications, has subsequently been reported to have a wide range of immunomodulatory effects and is widely used in the adjuvant therapy of autoimmune diseases and malignant tumors ( 14 , 15 ). Previous studies revealed that LMS promoted recovery of BM in patients who received chemotherapy by restoring the Th1/Th2 cell ratio to normal ( 16 ) and increasing the formation of granulocyte colony units ( 17 ). Efficacy of LMS treatment remains dose-dependent; which a low dose of LMS can induce dendritic cell maturation and stimulate T-cell activation but a high dose exerts inhibitory effects ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%